Knowledge and Attitude towards Complementary and Alternative Medicine in Najran City - Almansour, Ali; Alyami, Dawood; Alrashah, Ali; Alyami, Mansour Hussain; Al Hutaylah, Hassan; Masoud, Majed Ali; Al Dighrir, Abdullah Ali; Alkhamsan, Mohammed Hassan; Alalhareth, Abdullah Naji; Alyami, Ojaim Ali; Alrashah, Ali Ahmed Mohsen; Alfaifi, Noura; et al. (Journal of Ecohumanism, 2024)
Background and Objective: Psychosocial, cultural, and religious factors influence the use of complementary and alternative medicine (CAM); therefore, regular investigation of its prevalence and perceptions is essential. This study assessed the prevalence, demographic variations, knowledge, and perceptions of CAM use in Najran, Saudi Arabia. Methods: A cross-sectional survey was conducted in November 2024 targeting residents aged 18 years and older in Najran. The survey explored the types of CAM practiced, sources of information, and participants’ perceptions of CAM’s safety and efficacy compared with conventional medicine. Perceptions were assessed using a three-point Likert scale: Agree, Neutral, and Disagree. Results: This study included a total of 309 participants. The most used CAMs were herbal medicines (32%), massages (25.6%), and physiotherapy (24.3%). Demographic factors such as age, gender, nationality, and education significantly influenced CAM preferences. Higher educational levels were associated with increased physiotherapy, roqia, and acupuncture use. Male participants used cupping (Hijama) more frequently (p = 0.005), whereas aroma therapy was more common among older participants (p < 0.001). Camel milk and urine therapy were significantly more prevalent among Saudi nationals (p < 0.001). While 62.1% of the participants considered CAM safe, perceptions of its effectiveness relative to conventional medicine were mixed. Most participants (50%) reported improving their condition after using CAM. Conclusion: This study underscores the widespread use of CAM in Saudi Arabia, with herbal medicine, massage, and physiotherapy being the most commonly used modalities. Demographic factors, such as age, gender, nationality, and education, play a significant role in shaping CAM usage. While most participants reported positive experiences, their perceptions of CAM’s effectiveness compared with conventional medicine varied. These findings emphasize the need for regulated CAM practices and further research to ensure safe and effective integration into healthcare systems.